2009
DOI: 10.2106/jbjs.h.00762
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the Spine in Patients with Multiple Hereditary Exostoses

Abstract: The risk that a patient with multiple hereditary exostoses has a lesion within the spinal canal is much higher than previously suspected (27%). Because the potential exists for serious neurologic injury to occur, we have begun to use magnetic resonance imaging to screen all patients who have multiple hereditary exostoses at least once during the growing years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
86
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(91 citation statements)
references
References 26 publications
1
86
0
4
Order By: Relevance
“…Children with MHE who had had axial imaging had undergone nearly five surgeries on average, typically for the removal of symptomatic osteochondromas or placement of guided growth plates for angular deformity. In contrast to the rheumatoid population, routine plain radiographs will not necessarily show the pathology [6]. Roach et al [6] demonstrated that only 17 % of lesions were identifiable on radiographs.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Children with MHE who had had axial imaging had undergone nearly five surgeries on average, typically for the removal of symptomatic osteochondromas or placement of guided growth plates for angular deformity. In contrast to the rheumatoid population, routine plain radiographs will not necessarily show the pathology [6]. Roach et al [6] demonstrated that only 17 % of lesions were identifiable on radiographs.…”
Section: Discussionmentioning
confidence: 99%
“…This causes a disturbance in the negative feedback regulatory system, thus, leading to undifferentiated proliferation of chondrocytes in the metaphyseal region [23][24][25][26][27]. Their composition consists of healthy, lamellar bone and a cartilaginous cap, growing by endochondral bone formation at the metaphysis of long bones [4,6,28,29]. Malignant transformation to a chondrosarcoma has been reported in both the appendicular and axial skeleton, primarily in adults [30][31][32].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations